Error-prone DnaE2 Balances the Genome Mutation Rates in Myxococcus xanthus DK1622 - Peng, Ran; Chen, Jiang-he; Feng, Wan-wan; Zhang, Zheng; Yin, Jun; Li, Ze-shuo; Li, Yue-zhong (Frontiers in Microbiology, 2017)
DnaE is an alpha subunit of the tripartite protein complex of DNA polymerase III that is responsible for the replication of bacterial genome. The dnaE gene is often duplicated in many bacteria, and the duplicated dnaE gene was reported dispensable for cell survivals and error-prone in DNA replication in a mystery. In this study, we found that all sequenced myxobacterial genomes possessed two dnaE genes. The duplicate dnaE genes were both highly conserved but evolved divergently, suggesting their importance in myxobacteria. Using Myxococcus xanthus DK1622 as a model, we confirmed that dnaE1 (MXAN_5844) was essential for cell survival, while dnaE2 (MXAN_3982) was dispensable and encoded an error-prone enzyme for replication. The deletion of dnaE2 had small effects on cellular growth and social motility, but significantly decreased the development and sporulation abilities, which could be recovered by the complementation of dnaE2. The expression of dnaE1 was always greatly higher than that of dnaE2 in either the growth or developmental stage. However, overexpression of dnaE2 could not make dnaE1 deletable, probably due to their protein structural and functional divergences. The dnaE2 overexpression not only improved the growth, development and sporulation abilities, but also raised the genome mutation rate of M. xanthus. We argued that the low-expressed error-prone DnaE2 played as a balancer for the genome mutation rates, ensuring low mutation rates for cell adaptation in new environments but avoiding damages from high mutation rates to cells.